Micropuncture Studies of Sodium Tranport in the Remnant Kidney of the Dog THE EFFECT OF GRADED VOLUME EXPANSION - Wen, Sung-Feng (1973)
Proximal and distal tubule micropuncture studies were performed to examine the response to graded extracellular volume (ECV) expansion in 10 normal dogs (stage I), 11 dogs with a unilateral remnant kidney (stage II), and 7 dogs with a remnant kidney after removal of the contralateral kidney (stage III). Before ECV expansion in stage III, there was a suggestive reduction in proximal tubule as well as loop fractional reabsorption of sodium. After ECV expansion to 3% body weight proximal tubule reabsorption was depressed in all groups of animals, while little further inhibition was observed in this segment with additional expansion to 10% body weight. In contrast, the fraction of filtered sodium remaining in the distal tubule rose progressively in all three groups after graded ECV expansion, suggesting that the graded natriuretic response found in the final urine was largely due to a similar response in the loop of Henle rather than that in the proximal tubule. The distal tubule response of the remnant kidney in both stages II and III was greater than that in stage I. These data indicate that although enhanced sodium excretion per nephron in chronic renal failure may be related to uremia, its exaggerated response to ECV expansion is due, at least in part, to certain as yet unidentified intrarenal factors consequent to reduction in functioning renal mass.